1966
DOI: 10.1017/s0021859600067630
|View full text |Cite
|
Sign up to set email alerts
|

The value of liquid digested sewage sludge. III. The results of an experiment on barley

Abstract: In a trial laid out to compare the effects of liquid digested sludge with equivalent nitrogen and phosphate fertilizers as ‘Nitra-shell’ and superphosphate, growth data, and data of grain and straw yield were obtained.Liquid digested sludge increased the dry weight and shoot number at the ‘tillering’ stage, and dry weight and ear number at the flowering stage, more than equivalent fertilizer.By 13 May, sludge-treated plants had absorbed more nitrogen than fertilizer-treated plants. By 19 June this was reversed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1966
1966
1987
1987

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…at the high rate. These figures are lower than those obtained on a pure grass sward (Coker, 1966a) or those described by Baker (1960) and others. The lower response per lb.…”
Section: Discussion On T H E 1959-62 Trialscontrasting
confidence: 70%
See 1 more Smart Citation
“…at the high rate. These figures are lower than those obtained on a pure grass sward (Coker, 1966a) or those described by Baker (1960) and others. The lower response per lb.…”
Section: Discussion On T H E 1959-62 Trialscontrasting
confidence: 70%
“…If this interpretation is correct, then for a given amount of sludge nitrogen absorbed by the grass there was a greater dry weight increase than for the same amount absorbed from inorganic fertilizers. In a trial on barley (Coker, 19666) the author found that more nitrogen was absorbed from liquid digested sludge than from fertilizers during the early stages of growth, but the reverse applied later in the season; Thome (1962) showed that a given amount of fertilizer nitrogen applied early to barley produced a greater dryweight increase than later applications, by increasing the area of the leaves. Richardson (1934) concluded that grass absorbed ammonia directly, and Lewis (1936) found that ammonia nitrogen was more effective in increasing the grass dry-matter than nitrate nitrogen; the sludge which was used contained a high percentage of ammonia but little nitrate.…”
Section: White Clover Cocksfootmentioning
confidence: 99%
“…Nitrogen absorbed later in the growth period tends to increase herbage nitrogen concentrations with LDS. Coker (1966c) reported that the ammonium-N in LDS is taken up more rapidly than N in 'Nitro-Chalk'. It appears that the same effect occurs with LMDS.…”
Section: Discussionmentioning
confidence: 99%